The refugee game: The relationship between individual security expenditures and collective security - Jo\~ao Ricardo Faria; Andreas J. Novak; Aniruddha Bagchi; Timothy Mathews (Games, 2020)
This paper studies a three player hierarchical differential game (with a large country, a small country, and a terrorist organization), to analyze the actual European refugee situation. Terrorists may enter Europe as refugees, taking advantage of the Open Door Policy, to attack both countries. There are two scenarios: myopia and full awareness. Countries are myopic when they ignore each other's security efforts, and the terrorist group only considers the weakest link's security efforts. A comparison between the scenarios shows that for an extremely impatient large country, full awareness yields a greater level of security effort for the large country, a greater level of security effort for the small country, and more terrorist attacks. This is, however, an unstable equilibrium. The full awareness model with a patient large country is stable and lies in between the previous model and the myopic model. Although it yields larger investments in security, this still results in more terrorist attacks than the myopic model. Continental safety is higher in the myopic model than in the full awareness model.
Keywords: 330; differential game; externalities; international public goods; refugee crisis; terrorism